2022
DOI: 10.1080/07853890.2022.2140452
|View full text |Cite
|
Sign up to set email alerts
|

Performance of adenosine deaminase in detecting paediatric pleural tuberculosis: a systematic review and meta-analysis

Abstract: Background Paediatric pleural tuberculosis (TB) is a paucibacillary disease, which increases the difficulty of examination. We aimed to assess the performance of pleural fluid adenosine deaminase (ADA) in the detection of paediatric pleural TB. Methods PubMed, Web of Science Core Collection, Embase and Cochrane Library databases were searched up to 20 December 2021. We used the bivariate and hierarchical summary receiver operating characteristic models to compute pooled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
(37 reference statements)
0
2
0
1
Order By: Relevance
“…In tuberculosis, the amount of ADA appears to be related to the number of activated T lymphocytes responding to tuberculous antigens [68]. Besides the diagnostic role of serum ADA for patients with pulmonary TB, there has been increasing evidence that supports the importance of role of non-blood ADA for the diagnosis of patients with nonpulmonary TB, such as pleural ADA for pleural TB [69,70] and ascites ADA for abdominal TB [71]. Our study further expands the role of non-blood ADA for the diagnosis of non-pulmonary TB by showing the efficacy of ADA from CSF for the diagnosis of TBM.…”
Section: Discussionmentioning
confidence: 99%
“…In tuberculosis, the amount of ADA appears to be related to the number of activated T lymphocytes responding to tuberculous antigens [68]. Besides the diagnostic role of serum ADA for patients with pulmonary TB, there has been increasing evidence that supports the importance of role of non-blood ADA for the diagnosis of patients with nonpulmonary TB, such as pleural ADA for pleural TB [69,70] and ascites ADA for abdominal TB [71]. Our study further expands the role of non-blood ADA for the diagnosis of non-pulmonary TB by showing the efficacy of ADA from CSF for the diagnosis of TBM.…”
Section: Discussionmentioning
confidence: 99%
“…In 2019, Aggarwal et al [15] updated the sensitivity (0.92) and specificity (0.90) of ADA with conclusion as good biomarker for detecting pleural TB among adults, including 174 publications. Systematic review and meta-analysis also showed that ADA is good for detecting pediatric TP [16] .…”
Section: Introductionmentioning
confidence: 92%
“…In der Pleuraflüssigkeit zeigt sich häufig ein Exsudat mit lymphozytärer Pleozytose und normalem oder moderat erniedrigtem pH-Wert [5]. Zudem kann die Durchführung eines Interferon-Gamma-Release-Assays (IGRA) oder die Bestimmung der Adenosin-Desaminase aus dem Pleuraerguss diagnostische Hinweise geben [6,7]. Gesichert werden kann die Diagnose prinzipiell durch den Nachweis des Mycobacteriums tuberculosis im Pleurapunktat, wobei die Sensitivität von Mikroskopie, PCR und Kultur recht niedrig ist [8].…”
Section: Pleuritis Tuberculosaunclassified